Combination of Low Dose Ketamine, Paracetamol, and Tramadol for Opioid Induces Hyperalgesia in Lung Cancer with Intra Abdominal Metastases - Boyke Marthin Simbolon; Mual Kristian Sinaga (JAI (Jurnal Anestesiologi Indonesia), 2020)
Background: Opioid induced hyperalgesia or OIH is one of exaggerated response to pain secondary to using of the opioid itself. High dosage of opioid in long term (days to weeks) relate to increased OIH occurrence.Case: Female, 58 yrs, BMI 17.77, complained severe abdominal pain with NRS 8/10. Patient suffered from lung cancer stage 3 with intra abdominal metastases. Previously patient had received analgesic paracetamol 1gr TID, dexketoprofen 25mg TID, parecoxib 40mg OD, morphine 10mg BD and fentanyl patch 50 µg. Then fentanyl was given 25 µg IV twice with interval of 15 minutes. Patient still complained for pain and eventually pain severity increased to NRS 10/10. Afterwards patient was given low dose ketamin 0.1mg/kg slow IV push, paracetamol 1gr IV, and tramadol 50mg IV. After 15 minutes observation, pain decreased to NRS 5/10.Discussion: Decreasing total dose of opioid consumed may decresed OIH. It may be performed by improving analgesia by using combination of analgesic and intervention strategy.Conclusion: combination of low dose ketamine (0.1mg/kg), paracetamol, and tramadol may be benefit for patient with opioid induces hyperalgesia in lung cancer stage 3 with intra abdominal metastases.